Consumptive Behavior of Students Examined from the Perspective of E-Wallet Application Usage : Quantile Regression Analysis Method - Mahdiyah, Mahdiyah; Putri, Fildzah Rudyah; Dahlia, Mutiara (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2024)
The purpose of this research is to identify the consumptive behaviour of students from the perspective of e-wallet application usage. The research data is analyzed using the quantile regression method, which is a more specific regression method that can provide different estimator values at various quantile positions of the data. The respondents used in this study were 212 students. The results of the research show that the use of e-wallet applications is positively correlated with the consumptive behaviour of students. The relationship between the effect of using e-wallets and the consumptive behaviour of students varies at different quantile distribution levels. A larger regression coefficient value indicates a greater role of e-wallet usage in students' consumptive behaviour. The most significant role of e-wallet usage is seen at the 0.25, 0.75, 0.10, 0.50, and 0.90 quantiles in the distribution of students' consumptive behaviour. The variation in the results of this analysis demonstrates the flexibility of quantile regression and makes it more complex.